PRELIMINARY EVALUATION OF STRUCTURAL INTEGRITY OF THE SINGLE-PORT HDPE AND PARAFFIN GRAIN UNDER LOW TEMPERATURE CONDITIONS - Dias, Davi Gustavo Gomes; Andrianov, Artem; Barcelos Júnior, Manuel Nascimento Dias; Shynkarenko, Olexiy (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The main aim of the paper is to verify the feasibility of application of such common materials as paraffin and polyethylene for a small-sized single-port fuel grain in hybrid rocket motors at low temperature conditions. The simplified analytical method of stress analysis had been used to calculate the stresses in the grain and afterwards was verified with results obtained by the finite element method. The results of calculation and simulation revealed that the structural integrity of the paraffin at low temperatures is in doubt, while the polyethylene may carry the loads induced by cold conditions.